High temperature resistance of polymer-phosphazene concrete for 365 days - Tanyildizi, Harun; Asilturk, Erol (Elsevier Sci Ltd, 2018)
The performance of the polymer-phosphazene concrete subjected to elevated temperatures was investigated for 365 days in this study. Taguchi L-25 (5(6)) orthogonal array was used to find the parameters that affect compressive strength, ultrasonic pulse velocity and changes in weight by performing smaller number of experiments. Percentage of phosphazene in monomer (0%, 1%, 2%, 3% and 4%), curing period (28, 60, 90, 180 and 365 days), cement dosage (300, 350, 400, 450 and 500 kg/m(3)) and high temperature (20, 200, 400, 600 and 800 degrees C) were selected as experimental parameters. After the experimental design, samples with dimensions of 100 x 100 x 100 mm were produced. The samples were removed from the water and dried at 105 5 degrees C. Then, the vinyl acetate monomer with phosphazene was impregnated to samples for a 24 h period under atmospheric conditions. The polymerization of samples was performed at 60 degrees C for 4 h. Finally, these samples were exposed to temperatures of 200 degrees C, 400 degrees C, 600 degrees C and 800 degrees C. The ultrasonic pulse velocity, changes in weight and compressive strength experiments were applied to the samples. Furthermore, Scanning Electron Microscopy (SEM), Energy Dispersive X-ray (EDX) and X-ray powder diffraction (XRD) analyses of specimens were conducted. The results showed that the best values were obtained from samples exposed to 400 degrees C. Thus, this study has been shown that the polymer-phosphazene concrete can be used in structures that can be exposed to 400 degrees C. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Concrete; Polymer; Phosphazene; Elevated temperature; Mechanical properties; SEM; EDX; XRD